Educational inequality and intergenerational mobility in Latin America: A new database - Guido Neidhöfer; Joaquín Serrano; Leonardo C. Gasparini (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2017)
The causes and consequences of the intergenerational persistence of inequality are a topic of great interest among various fields in economics. However, until now, issues of data availability have restricted a broader and cross-national perspective on the topic. Based on rich sets of harmonized household survey data, we contribute to filling this gap computing time series for several indexes of relative and absolute intergenerational education mobility for 18 Latin American countries over 50 years, and making them publicly available. We find that intergenerational mobility has been rising in Latin America, on average. This pattern seems to be driven by the high upward mobility of children from low-educated families; at the same time, there is substantial immobility at the top of the distribution. Significant cross-country differences are observed and are associated with income inequality, poverty, economic growth, public educational expenditures and assortative mating.
Keywords: D63; I24; J62; O15; 330; Inequality; Intergenerational Mobility; Equality of Opportunity; Transition Probabilities; Assortative Mating; Education; Human Capital; Latin America